2020
DOI: 10.3390/cells9010109
|View full text |Cite
|
Sign up to set email alerts
|

DAF-16/FoxO in Caenorhabditis elegans and Its Role in Metabolic Remodeling

Abstract: DAF-16, the only forkhead box transcription factors class O (FoxO) homolog in Caenorhabditis elegans, integrates signals from upstream pathways to elicit transcriptional changes in many genes involved in aging, development, stress, metabolism, and immunity. The major regulator of DAF-16 activity is the insulin/insulin-like growth factor 1 (IGF-1) signaling (IIS) pathway, reduction of which leads to lifespan extension in worms, flies, mice, and humans. In C. elegans daf-2 mutants, reduced IIS leads to a heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 152 publications
(211 reference statements)
1
77
0
2
Order By: Relevance
“…In addition, FoxO protein is inactivated by major carcinogenic signals such as phosphatidylinositol-3 kinase pathway and MAP kinase . FoxOs regulate the expression of many genes to control many cell functions, such as cell growth (Niimi et al, 2019), survival (Hassell, 2019), metabolism and antioxidant status (Zečić & Braeckman, 2020). However, recent studies have shown new and unknown functions of FoxO in cancer treatment and promotion, which shows that FOXO factor, has complex roles in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FoxO protein is inactivated by major carcinogenic signals such as phosphatidylinositol-3 kinase pathway and MAP kinase . FoxOs regulate the expression of many genes to control many cell functions, such as cell growth (Niimi et al, 2019), survival (Hassell, 2019), metabolism and antioxidant status (Zečić & Braeckman, 2020). However, recent studies have shown new and unknown functions of FoxO in cancer treatment and promotion, which shows that FOXO factor, has complex roles in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of pqm-1 suppresses DAF-2 activity, which can inactivate daf-16 transcription, probably affecting the resistance of parasites to AgNP exposure as well as accelerated cell death. The decreased expression of pqm-1 is related to aging [ 60 , 133 ]. Likewise, the phospholipase D gene pdl-1 was up-regulated by a 3.51 z-score, and it is also involved in the DAF-16 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of oxidative stress responses and proteostasis, as well as modulation of metabolic processes, are also key downstream effects of DAF-16 activation, and the majority of genes within the clusters we identified are also known to be upregulated by DAF-16 (Harris et al, 2020;Honda & Honda, 1999;Li & Zhang, 2016;McElwee, Bubb, & Thomas, 2003;Webb et al, 2016;Zečić & Braeckman, 2020). Significantly upregulated oxidative stress response genes included sodh-1, catalase genes ctl-1 and ctl-3, and members of the cytochrome P450 and glutathione S-transferase families ( Figure 4F), all of which are DAF-16 targets (Webb et al, 2016).…”
Section: Rna Sequencing Demonstrates Induction Of Protective Stress Rmentioning
confidence: 91%